DNA Switches: G‐Quadruplex‐Stimulated Optical and Electrocatalytic DNA Switches (Small 30/2015). Issue 30 (August 2015) - Aizen, Ruth; Golub, Eyal; Trifonov, Alexander; Shimron, Simcha; Niazov‐Elkan, Angelica; Willner, Itamar
<x xml:space="preserve">Abstract</x> The stabilization of G‐quadruplexes by means of K+ ions, and the separation of the nanostructures by 18‐crown‐6 or [2.2.2] cryptand, provide means to assemble switchable photonic or electrocatalytic molecular systems. On page 3654, this is exemplified with the construction of a G‐quadruplex‐based photonic "DNA spring" by I. Willner and co‐workers, and by the assembly of a switchable hemin/G‐quadruplex nanostructure on an electrode, acting as an electrocatalytic "ON"/"OFF" switch towards the reduction of H2O2. Image designed by Guoyuan Tan.